Effect of Mediterranean diet on body mass index and fatigue severity in patients with multiple sclerosis: A systematic review and meta-analysis of clinical trials - Amir Reza Moravejolahkami; Mehdi Shakibaei; Manoj Sharma; Masoud Mohammadnezhad; Sri Lakshmi Sravani Devarakonda (Heliyon, 2024)
Background: Recent studies imply that Mediterranean Diet (MeD) may play an important role in the management of Multiple Sclerosis (MS). This meta-analysis aimed to evaluate the effectiveness of MeD in addressing MS-related complications. Methods: A thorough search was performed in MEDLINE (PubMed), Scopus, EMBASE, ScienceDirect, Google Scholar, Web of Science, and the Central Cochrane Library, covering trials published until September 2023. The quantitative data were synthesized using random effect models through STATA14. Results: After analyzing 228 entries, we found five Randomized Controlled Trials (RCTs) with a total of 540 participants, who had an average disease duration of 8.5 years. The combined effect size revealed a decrease in Body Mass Index (BMI) (Weighted Mean Difference [WMD] = −0.88 kg/m2; 95 % Confidence Interval [CI] = −1.68, −0.08; P = 0.030). There was also a non-significant marginal improvement in fatigue severity (WMD = −8.29; 95 % CI = −16.74, 0.16; P = 0.054). Conclusion: Adherence to MeD may improve BMI and fatigue severity in MS patients. Further RCTs are needed to confirm the current results.